CHONDROGENIC DIFFERENTIATION OF HUMAN WHARTON'S JELLY MESENCHYMAL STEM CELLS USING MICROCONTACT PRINTING METHOD - AGAROSE STAMP - Hani'ah Arum Saputri, Dinda
Degenerative diseases associated with cartilage damage can be treated with cell-based therapy. Chondrocytes as a cell therapy material can be obtained from Mesenchymal Stem Cells (MSC) through a chemical stimulus i.e. Growth Factor (GF), but it requires a large cost of production especially for long-term culture. Another alternative that can be used was the microcontact printing (?CP) method which uses a mechanical stimulus. Fibronectin (Fn) was commonly used as an ink in the ?CP method because it can induce adherence, migration, proliferation, and differentiation of cells. This study aims to determine the role of ?CP-agarose stamp method using Fn to induce chondrogenic differentiation of hWJ-MSC with increasing GAG levels, increasing the expression of COL2 and SOX9 genes also increasing the presence of type II collagen. In this study, the ?CP method was used agarose polymers to transfer fibronectin ink with a line pattern of 500 ?m and 1000 ?m onto the coverslip substrate. Human Wharton's Jelly (hWJ) cells were isolated from the umbilical cord, expanded and characterized based on MSC criteria, then chondrogenic differentiation was analyzed through the expression of COL2 and SOX9 genes using the Real Time-quantitative Polymerase Chain Reaction (RT-qPCR) method, the presence of collagen II using the Immunocytochemistry (ICC) method, and the levels of Glycosaminoglycan (GAG) using the alcian blue quantification method, for 7, 14, and 21 days. Micropattern using the ?CP-agarose stamp method resulted in a size of 375 ?m for 500 ?m mold and 819 ?m for 1000 ?m mold. Fibronectin-micropatterned (FnM) was able to make cells grow only on the pattern. The results of cell characterization showed that the hWJ cells used in this study belonged to MSC. GAG levels on both sizes of FnM showed the optical density (OD) value increased significantly compared to the control on day 21. However, COL2 gene expression was decreased significantly on FnM 819 ?m on day 21 while SOX9 gene expression was not significantly different compared to controls on day 14 and day 21. Visualization of type II collagen with ICC showed that FnM increased the presence of type II collagen compared to controls starting on day 14 for 819 ?m and increasing at day 21 for 375 ?m and 819 ?m. Based on the results of this study, it can be concluded that FnM using the ?CP-agarose stamp method can increase the chondrogenic differentiation of hWJ-MSC by increasing the levels of GAG and visualization of type II collagen protein even though it reducing the expression of COL2 gene and does not affect SOX9 gene expression compared to control.